Pengaruh Teknologi dan Globalisasi Terhadap Sistem Hukum dan Identitas Sosial Masyarakat - L, Lazarus (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to explore the impact of technology and globalization on the legal system and social identity of communities. The background highlights the significant influence of information technology and the global interconnectedness of societies, reshaping legal frameworks and altering social identities. The urgency of this research lies in understanding the challenges and opportunities posed by technological advancement and globalization, particularly in the context of developing countries like Indonesia. The methodology involves a comprehensive review of literature and empirical data analysis to assess the implications of these phenomena on legal systems and societal identities. The findings indicate a complex interplay between technology, globalization, legal frameworks, and social identities, with both positive and negative consequences. While technology and globalization facilitate access to legal information and cross-cultural exchanges, they also raise concerns regarding privacy, security, and the preservation of local cultural identities. Therefore, proactive measures are necessary to harness the benefits of technology and globalization while safeguarding legal integrity and preserving social cohesion.